Розріджений бозе-газ в класичному середовищі при низьких температурах - Pastukhov, V. (Publishing house "Academperiodika", 2020)
The properties of a dilute Bose gas with the non-Gaussian quenched disorder are analyzed. Being more specific, we have considered a system of bosons immersed in the classical bath consisting of the non-interacting particles with infinite mass. Making use of perturbation theory up to the second order, we have studied the impact of environment on the ground-state thermodynamic and superfluid characteristics of the Bose component.